Stimulus and Fiscal Consolidation: The Evidence and Implications - Dean Baker; David Rosnick (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
This paper examines the evidence on the impact of stimulus and fiscal consolidation in the context of a severe economic slump like the Great Recession. The first part reviews some of the major works on this topic in the last decade. It notes that the research clearly points in the direction of stimulus increasing growth during a prolonged slump. The second part examines the impact of changes in government consumption and investment on growth, using data from advanced countries since 1980. Consistent with most prior literature it finds that increases in government spending during downturns lead to increases in growth. It then constructs simulations for the period since the Great Recession showing multipliers in the neighborhood of 1.5. The third part notes new evidence suggesting that potential GDP appears to have fallensharply as a result of the downturn. A full model of the impact of stimulus would have to incorporate this effect which is likely to be large relative to the size of the stimulus.
urn:nbn:de:101:1-2014080818100
Keywords: 330